A Case of Adenoid Cystic Carcinoma Mimicking a Bartholin Cyst and Literature Review. (26th March 2018) - Goh, Siew Pei; McCully, Brian; Wagner, Matthew Kyle
Abstract : Adenoid cystic carcinoma of the Bartholin Gland (BG-ACC) is a rare form of vulval cancer with only approximately 350 reported cases since 1864. A review of available literature and case reports suggests an aggressive nature with protracted clinical symptoms and a tendency for local recurrence despite adequate surgical excision with or without adjuvant radiotherapy. Survival rates of 71% and 59% are reported at five and ten years. This case report endeavours to add to our body of knowledge regarding this rare disease and thus help broaden and improve our understanding of management and treatment success.